Dietary diversity and associated factors among children (6-23 months) in Gedeo zone, Ethiopia: cross - sectional study - Wondwosen Molla; Dirshaye Argaw Adem; Ruth Tilahun; Seid Shumye; Robel Hussen Kabthymer; Daniel Kebede; Nebiyu Mengistu; Getnet Melaku Ayele; Dawit Getachew Assefa (BMC, 2021)
Abstract Introduction Different foods and food groups are good sources for various macro- and micronutrients. Diversified diet play an important role in both physical and mental growth and development of children. However, meeting minimum standards of dietary diversity for children is a challenge in many developing countries including Ethiopia. Objective To assess dietary diversity and associated factors among children (6-23 months) in Gedieo Zone, Ethiopia. Method Community based cross-sectional study was carried out at Gedieo Zone, Ethiopia, from January to March 15, 2019. Multi-stage sampling technique was used to get a total of 665 children with the age of between 6 and 23 months from their kebeles. Data was collected by using face-to-face interview with structured questionnaire. Data was entered into Epidata version 3.1 and exported to Statistical Package for the Social Sciences (SPSS) version 23.0 for analyses. Variables having p < 0.25 at bivariate analysis were fitted to multivariable analysis. Multivariable logistic regression model was used at 95% confidence interval and with P-Value < 0.05. Bivariate. Result A total of 665 children were participated with response rate of 96.2%. Only 199(29.9%) of children were met the minimum requirements for dietary diversity. Age of children [AOR 4.237(1.743-10.295))], Educational status [AOR 2.864(1.156-7.094)], Number of families [AOR 2.865(1.776-4.619))] and household wealth index [AOR4.390(2.300-8.380)] were significantly associated with Dietary Diversity of children. Conclusion Only, one out of four children aged of 6-23 months attained the minimum dietary diversity score. Children from low socioeconomic status and mothers with no formal educational attainment need special attention to improve the practice of appropriate feeding of children.